CENFED spearheads Professional Development Programmes in the East Coast - UMP, PNC
The Centre for Continuing Education & Professional Development (CENFED) of University Malaysia Pahang (UMP) was founded for the main purpose of delivering training and re-training programmes, as well as continuing education, to the industries and professionals, in particular, and to the public at large, in general. And since its establishment, CENFED has trained more than 4,000 individuals nationwide.